Hungarian Monitoring, 4 February 1990 . [Magyar rádiófigyelő], 1990. február 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Large demonstration in Moscow against CPSU's monopoly on power - Bulgarian domestic politics - West German party leaders visit their GDR partners - Talks in Vilnius between Azerbaijan and Armenia in danger Domestic Affairs: - László Tőkés receives honorary doctorate - Géza Domokos's statement on minorities to a Bucharest daily - Election: party programs, the coalition question, and scandals - An eye-witness to the movements in Brasov in 1987 speaks Economy: - Medgyessy's speech at Davos Külpolitika: - Nagy tüntetés Moszkvában az SZKP hatalmi monopóliuma ellen - A bulgáriai belpolitikai helyzet - Nyugatnémet pártvezetők NDK-beli partnereiknél - Veszélyben a vilniusi azerbajdzsán-örmény tárgyalások Belpolitika: - Tőkés Lászlót díszdoktorrá avatják - Domokos Géza nyilatkozik egy bukaresti lapnak kisebbségügyben - Választás: pártprogramok, a koalíció kérdése és botrányok - Egy szemtanú nyilatkozik a 87-es brassói megmozdulásról Gazdaság: - Medgyessy felszólalása a világgazdasági fórumon